Imagens que representam pessoas em livros didáticos de Física: Uma proposta de leitura de imagens para estudantes a partir da Semiótica Peirceana - Silva, Maria Ruthe Gomes da (2020)
The textbook, despite the numerous resources available for teaching and learning physics, remains one of the most used tools by teachers, teachers, and students in the public school system. In addition to being one of the most investigated media in research on science teaching. Much of this research is aimed at investigating the correction of conceptual contents and methodologies, and there is a lack of studies that seek to establish relationships between the textbook and to whom most of these materials are intended - students. Within the scope of research relating textbooks and students, one of the most recent results pointed out that there are differences in interests in relation to gender (female and male). One of these differences shows that girls are more concerned with textbook images than boys. Considering these results, and in view of the increased interest in investigating the factors that have limited/prevented/silenced the participation of women in physics, the objective of this dissertation is to investigate how students in the basic education network read images that represent people broadcast in Physics Textbooks and how gender (female and male) is taken into account. To achieve our goal, we developed an activity whith image in a first-year high school class at a public school, in the city of Campina Grande - PB. The activity was built on the assumptions of the General Theory of Signs by Charles Sanders Peirce. From the activity whith image, we realized that the students did not make a direct relationship between the gender (female and male) of characters represented with the role they were playing. The main justification given by the students is that the images were in the book because they were related to the content that was being addressed in the chapter. We understand that this study is pertinent both to mitigate the existing gaps regarding the researches that link textbook with students, and to understand how students read images that represent people in Physics Textbooks and attribute meaning in relation to gender (female and male). In addition, this dissertation can serve as a starting point for teachers who want to develop works that relate textbooks with students from the basic education network in order to involve the perspectives and demands of students in the literature in this area.